2006
DOI: 10.1111/j.1744-7348.2006.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of tomato‐infecting begomoviruses and Bemisia tabaci biotypes in Morocco

Abstract: Tomato yellow leaf curl virus (TYLCV) and tomato yellow leaf curl Sardinia virus (TYLCSV) (genus Begomovirus, family Geminiviridae) as well as their whitefly vector Bemisia tabaci were reported from the south-west and central regions of Morocco. To establish a more comprehensive view of tomato begomoviruses and B. tabaci biotypes throughout Morocco, 32 tomato fields were surveyed for tomato yellow leaf curl disease (TYLCD) symptoms in southern and northern regions, and 54 samples of leaves from cultivated plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 18 publications
6
28
0
1
Order By: Relevance
“…Individuals belonging to group B were not detected elsewhere in southern France. The genetic groups B and Q were also detected in other Mediterranean countries but with various ratios and sometimes overlapping distribution areas as shown in Italy (Cavalieri et al, 2004;Parella et al, 2004), southern Spain (Pascual and Callejas, 2004), Canary Islands (Gobbi et al, 2003) and Morocco (Tahiri et al, 2006). The lack of any specific and distinct geographical pattern is consistent with the invasiveness of these groups and stands in contrast with the large geographic structuring detected with Asia-Pacific populations in their native region .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Individuals belonging to group B were not detected elsewhere in southern France. The genetic groups B and Q were also detected in other Mediterranean countries but with various ratios and sometimes overlapping distribution areas as shown in Italy (Cavalieri et al, 2004;Parella et al, 2004), southern Spain (Pascual and Callejas, 2004), Canary Islands (Gobbi et al, 2003) and Morocco (Tahiri et al, 2006). The lack of any specific and distinct geographical pattern is consistent with the invasiveness of these groups and stands in contrast with the large geographic structuring detected with Asia-Pacific populations in their native region .…”
Section: Discussionmentioning
confidence: 97%
“…For some individuals, an 817 bp fragment was amplified and sequenced following cloning as described by Tahiri et al (2006). For others, a 755 bp sequence was determined directly from a PCR product amplified with primers C1 (Frohlich et al, 1999) and 801c, 5 0 -CACAMCTCTTTAAAACTRTGA-3 0 ; amplification conditions were as described by Tahiri et al (2006) but with 35 cycles at 95 1C for 60 s, 54 1C for 45 s and 72 1C for 30 s. Sequences were aligned with Genbank CO1 sequences that showed the highest nucleotide identity, using the Optimal Alignment method of DNAMAN (version 5.0; Lynnon BioSoft, Quebec, Canada). A phylogenetic tree was set up with a Jukes and Cantor distance matrix using the neighbour-joining method (NJ; Saitou and Nei, 1987) as implemented in the DNAMAN software.…”
Section: Co1 Sequencingmentioning
confidence: 99%
“…The viral species identified were TYLCV and Tomato yellow leaf curl Sardinia virus (TYLCSV); the isolates corresponding to both species were in this case in closest relationship to isolates from Spain (Monci et al, 2000). TYLCD was the principal cause of the important losses registered in 1999 in the region of Agadir and reduction of 50% of the tomato cultivated area in El Jadida (Tahiri et al, 2007). The presence of both TYLCV and TYLCSV was subsequently reported in the Agadir region (Sedegui et al, 2002).…”
Section: Introductionmentioning
confidence: 91%
“…The presence of both TYLCV and TYLCSV was subsequently reported in the Agadir region (Sedegui et al, 2002). Analysis of samples harvested in [2001][2002] showed that infection of tomato crops was more common in the southwest than in the north (Tahiri et al, 2007). The sequence analysis revealed the existence of the Spanish strain of TYLCSV and of two genetically different strains of TYLCV.…”
Section: Introductionmentioning
confidence: 99%
“…In-depth ecological knowledge about both pests and their natural enemies in the country of origin may help toward better preparedness and to develop more robust cropping systems. This may apply to both already introduced pests and vectored diseases such as Tuta absoluta (Desneux et al 2010;Zappalà et al 2013), B. tabaci (Tahiri et al 2006), tomato yellow leaf curl virus (TYLCV), Plutella xylostella, and its parasitoids (Sarfraz et al 2005), and to potential invasive species such as Bactrocera fruit flies (Stephens et al 2007). Robust cropping systems were already developed and tested in the tropics against a range of such pests (Licciardi et al 2008;Vayssieres et al 2009).…”
Section: Insectsmentioning
confidence: 99%